Do markets erode social responsibility? - Björn Bartling; Roberto Weber; Lan Yao (University of Zurich, Department of Economics, 2014)
This paper studies socially responsible behavior in markets. We develop a laboratory product market in which low-cost production creates a negative externality for third parties, but where alternative production with higher costs mitigates the externality. Our first study, conducted in Switzerland, reveals a persistent preference among many consumers and firms for avoiding negative social impact in the market, reflected both in the composition of product types and in a price premium for socially responsible products. Socially responsible behavior is generally robust to varying market settings, such as increased seller competition and limited consumer information, and it responds to costs and prices in a manner consistent with a model in which positive social impact is a utility-enhancing feature of a consumer product. In a second study, we investigate whether market social responsibility varies across societies by comparing market behavior in Switzerland and China. While subjects in Switzerland and China do not differ in their degree of social concern in non-market contexts, we find that low-cost production that creates negative externalities is significantly more prevalent in markets in China. Across both studies, consumers in markets exhibit less social concern than subjects in a comparable individual choice context, though the difference is much smaller in Switzerland.
Keywords: C92; D03; D62; M14; 330; Social responsibility; markets; externalities; competition; cultural differences